a) We have to find the equation of the quadratic expression.
We have the expression:
![x^2+2x+y^2-4y=4](https://img.qammunity.org/2023/formulas/mathematics/high-school/7rpfkzqe39igrxouhzywfiv050dmi12p5k.png)
We can grouop the terms for y and x and find the constants we need to form a perfect binomial (completing the squares):
![\begin{gathered} (x^2+2x+1-1)+(y^2-4y+4-4)=4 \\ \lbrack(x+1)^2-1\rbrack+\lbrack(y-2)^2-4\rbrack=4 \\ (x+1)^2+(y-2)^2-1-4=4 \\ (x+1)^2+(y-2)^2=4+1+4 \\ (x+1)^2+(y-2)^2=9 \\ (x+1)^2+(y-2)^2=3^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/5saegaarzzcwn7bmrmanr5i4j6aanpmrqo.png)
The expression results in a circumference of radius 3 with the center ar (-1,2).
c) If we have the equation:
![2x^2+2y^2+3x-5y=2](https://img.qammunity.org/2023/formulas/mathematics/high-school/dtzw9hz6odyf6wxcb2wmf5mybwunjfzp3v.png)
We can solve this as:
![\begin{gathered} 2(x^2+y^2+(3)/(2)x-(5)/(2)y)=2 \\ \lbrack x^2+(3)/(2)x+((3)/(4))^2-((3)/(4))^2\rbrack+\lbrack y^2-(5)/(2)y+((5)/(4))^2-((5)/(4))^2\rbrack=1 \\ \lbrack(x+(3)/(4))^2-(9)/(16)\rbrack+\lbrack(y-(5)/(4))^2-(25)/(16)=1 \\ (x+(3)/(4))^2+(y-(5)/(4))^2=1+(9)/(16)+(25)/(16) \\ (x+(3)/(4))^2+(y-(5)/(4))^2=(16+9+25)/(16) \\ (x+(3)/(4))^2+(y-(5)/(4))^2=(50)/(16) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/jnu1ttszr6dxxws0w75vpsf6yt09xi4ink.png)
We can calculate the radius as:
![r=\sqrt[]{(50)/(16)}=\sqrt[]{(2\cdot25)/(16)}=\sqrt[]{2}\cdot(5)/(4)=(5)/(4)\sqrt[]{2}](https://img.qammunity.org/2023/formulas/mathematics/high-school/44v6q76y2bv4c6rwyqzuc59pyb6imx8ccf.png)